Determining factors of environmental management practices in portuguese local entities - Ribeiro, Verónica (2013)
Purpose: The aim of this paper is to analyse the development of environmental management practices by Portuguese local entities and their determining factors. Design/methodology/approach: The data were collected by sending a postal questionnaire. In order to measure the degree of development of environmental management practices an index of environmental management practices (EMPI) was developed, which reflects the extent to which a set of 16 environmental management practices have been implemented by the entities included in the sample. Four variables are considered in this study as possible factors that drive the development of environmental management practices by local entities, namely type of entity, size, proactive environmental strategy and Local Agenda 21 Findings: Results indicate the degree of development of environmental management practices in Portuguese local entities is low. Additionally, entity size, the adoption of proactive environmental strategies and the implementation of Local Agenda 21 are explaining factors of the degree of development of such practices. Originality/value: This study adds to the international research on environmental management in public sector by providing empirical data from a country, Portugal, where empirical evidence is still relatively limited.